STRATEGI SELF PRESENTATION PADA KARYAWAN BANK BAGIAN CUSTOMER SERVICE - Tri Muji Ingarianti, Stefi Rizki Widya dan (University of Muhammadiyah Malang, 2013)
Customer service merupakan jembatan penghubung bank dengan nasabah yang dituntut untuk memberikan pelayanan dengan mutu terbaik dengan memperlihatkan performa diri yang positif agar terkesan sebagai seseorang yang bersahabat, ahli, serta berpengalaman dalam menawarkan jasa bank. Penelitian ini bertujuan untuk mengetahui strategi self presentation pada karyawan bank bagian customer service. Jenis penelitian ini adalah deskriptif kuantitatif. Sampel penelitian sebanyak 60 customer service bank dengan teknik Incidental Sampling. Metode pengumpulan data menggunakan angket dengan metode analisa data menggunakan prosentase. Hasil penelitian ini menunjukkan 14 customer service (23,33%) menggunakan strategi ingratiation ketika melayani nasabah, 13 (21,67%) strategi self promotion, 11(18,33%) strategi supplification, 9 (15%) strategi aligning actions, 6 (10%) strategi exemplification, 4 (6,67%) strategi self handicapping, 3 (5%) strategi altercasting, serta 0% strategi intimidation.Kata kunci: Strategi Self Presentation, Customer Service BankCustomer service is a bridge for bank to the customer so they are required to provide the highest quality service in order to maintain the relationship and the bank remains a good image in the eyes of the customer. The purpose of this study was to determine self-presentation strategies on the bank's customer service employees. This type of research is descriptive quantitative approach. The sample of 60 customer service bank. Sampling technique used is incidental sampling. Instruments used to collect the data was questionnaires and data analysis methods are percentages.These results indicated that 14 customer service (23.33%) used the strategy of ingratiation when serving customers, 13 (21.67%) strategy of self promotion, 11(18.33%) supplification strategies, 9 (15%) strategy of aligning actions, 6 (10%) strategy of exemplification, 4 (6.67%) selfhandicapping strategies, 3 (5%) altercasting strategies, and 0% onintimidation strategies.Keywords: Self-Presentation Strategies, Bank Customer Service